A Model to Promote Public Health by Adding Evidence-Based, Empathy-Enhancing Programs to All Undergraduate Health-care Curricula - Van Winkle, Lon J.; Schwartz, Brian D.; Michels, Nicole (Frontiers in Public Health, 2017)
Fostering empathy in future healthcare providers through service-learning is emerging as central to public health promotion. Patients fare better when their care-givers have higher relationship-centered characteristics such as the ones measured by the Jefferson Scale of Empathy. Unfortunately, these characteristics often deteriorate during healthcare professional training. Nevertheless, growing literature documents how we can promote empathy, and other patient-centered characteristics, throughout healthcare professional students’ undergraduate education. As for proven treatment plans, we believe we should also use evidence-based guidelines to foster relationship-centered characteristics in our students when training them to practice as part of an interdisciplinary healthcare team.